Efficacy and safety of oral NEPA (Netupitant/Palonosetron), the first fixed-combination antiemetic, in patients with gynecological cancers receiving platinum-based chemotherapy - Bošnjak, Snežana M.; Jordan, Karin (International journal of gynecological cancer, 2018)
Objective Patients with gynecological cancers are at high risk for chemotherapy-induced nausea and vomiting (CINV) after platinum-based chemotherapy (CT). NEPA (300-mg netupitant, 0.50-mg palonosetron) is the first oral fixed-combination antiemetic. Pivotal trials demonstrated the superiority of oral NEPA over intravenous palonosetron in preventing CINV after highly emetogenic (anthracycline-cyclophosphamide–based [AC] and cisplatin-based [non-AC]) CT. This post hoc subset analysis considered patients with gynecological cancer receiving cisplatin- or carboplatin-based CT from 1 pivotal trial and from 1 multicycle safety trial to evaluate the efficacy of oral NEPA in preventing CINV. - Methods Single-dose NEPA was given before CT in combination with dexamethasone. The efficacy end points for the acute (0–24 hours), delayed (25–120 hours), and overall (0–120 hours) CINV phases after CT included complete response (CR; no emesis, no rescue medication) and no significant nausea (<25 mm on a 0- to 100-mm visual analog scale). Safety was also assessed. - Results For cisplatin-induced CINV, NEPA achieved high CR rates (acute phase: >90%; delayed, overall phases: ≥85%). For carboplatin-induced CINV, NEPA was also highly effective, with high acute, delayed, and overall CR rates (cycle 1: >75%; cycles 2–4: >95%). No significant nausea rates were more than 90% and more than 80% in the acute and delayed phases, respectively, for patients receiving cisplatin or carboplatin. NEPA was well tolerated. - Conclusions Results suggest that oral NEPA is effective and safe in preventing CINV in patients with gynecological cancers treated with cisplatin- or carboplatin-based CT. Single fixed-combination NEPA is a convenient option for CINV prevention in high-risk CINV patients.
Gesehen am 02.04.2019